Dynamic analysis of arch dams considering fluid-structure interaction - Vela Calderón, Yoshi Raul (2022)
The social, economic, and environmental consequences of the failure of an arch dam make it essential to evaluate its dynamic response to mitigate the risk of a disaster. Since the slenderness and flexibility of these dams tend to increase the fluid-structure interaction during an earthquake, this work compares the dynamic response of a hypothetical arch dam in the Marañón river, in northern Perú, for both full and empty-reservoir conditions. Three formulations were used to estimate the hydrodynamic pressures: Westergaard’s added mass, Eulerian and Lagrangian. The comparisons were performed for earthquakes of distinct seismogenic sources, previously matched to a uniform hazard spectrum with a return period of 10000 years. The finite element method was used to derive the seismic demands of the dam-reservoir-foundation system in COMSOL Multiphysics software, carrying out time-history analyses assuming linear elastic behavior of the dam and foundation domains and a massless foundation approach, ignoring the effect of waves propagation in the foundation but considering its stiffness. The results show that the Lagrangian and Eulerian formulations produce similar seismic demands, while Westergaard’s added mass formulation is conservative. The full-reservoir condition generally increases the seismic demands, but the results will depend on the boundary conditions assumed for the fluid and the characteristics of the earthquake, among other factors. Earthquakes matched to the same uniform hazard spectrum do not necessarily produce equal dynamic responses.